Human heritable genome editing and its governance: views of scientists and governance professionals - R. Jean Cadigan; Margaret Waltz; John M. Conley; Rami M. Major; Elizabeth K. Branch; Eric T. Juengst; Michael A. Flatt (New Genetics and Society)
Heritable human genome editing has garnered significant attention in scholarly and lay media, yet questions remain about whether, when, and how heritable genome editing ought to proceed. Drawing on interviews with scientists who use genome editing in their research and professionals engaged in human genome editing governance efforts, we examine their views on the permissibility of heritable genome editing and the governance strategies they see as necessary and realistic. For both issues, we found divergent views from respondents. We place the views of these scientists and governance professionals within the context of the larger bioethical discussion of heritable genome editing governance, along a continuum of hard to soft approaches. These respondents’ views highlight the challenges of various hard forms of governance and the potential virtues of soft governance approaches.